M141. INDIVIDUALS WITH SCHIZOTYPAL TRAITS SHOW A UNIQUE PATTERN OF CAUDATE ACTIVATION IN PROSPECTION OF POSITIVE EMOTION COMPARED TO HEALTHY CONTROLS. (18th May 2020) - Zhang, Ruiting; Yang, Zhuoya; Huang, Jia; Wang, Yongming; Zhou, Hanyu; Wang, Yi; Lui, Simon S Y; Cheung, Eric; Ongur, Dost; Holt, Daphne; Chan, Raymond
Abstract: Background: Prospection, the ability to simulate future scenarios and pre-experience future feelings, plays a fundamental role in anhedonia and motivation. Empirical findings have suggested that a wide range of patients who experience anhedonia, with schizophrenia, autism and major depression, exhibit prospection impairment. Altered brain responses while envisioning future events have also been observed in these clinical samples. However, it remains unclear whether similar abnormalities are exhibited by individuals with schizotypal traits (ST), autistic traits (AT) and subsyndromal depressive symptoms (SD). Methods: The Schizotypal Personality Questionnaire, Autism-Spectrum Quotient, and Patient Health Questionnaire-9 were administered to a group of 2904 college students. Based on the cut-off points of each scale, a final sample of 27 individuals with ST, 34 with AT, 31 with SD, and 35 with low levels of all subclinical features (controls) were recruited. Participants performed a Prospection Task in a 3T MRI scanner and completed the Temporal Experience of Pleasure Scale (TEPS) after the brain scan. The Prospection task included three conditions: positive prospection, neutral prospection, and control imagination. Contrasts examining general prospection [positive prospection + neutral prospection – control imagination], positive prospection [positive prospection- control imagination], neutral prospection [neutral prospection-control imagination], and positive emotion [positive prospection – neutral prospection] were defined. Group comparisons were conducted to measure brain activation in all contrasts using a threshold of p<0.001, Familywise error corrected. Results: Increased activation of the task-positive network, including regions of the bilateral inferior parietal gyrus, the middle frontal gyrus, and the inferior frontal gyrus, was observed in individuals with ST, AT and SD, for the general prospection contrast, compared to controls. Both individuals with ST and AT exhibited reduced activation of the medial frontal gyrus, the posterior cingulate cortex, the precuneus, and the hippocampus (the "core network"/default mode network) for the general prospection contrast, compared to controls. However, only individuals with ST exhibited increased activation of the bilateral caudate for the positive emotion contrast. Moreover, activation of the bilateral caudate in ST individuals was negatively correlated with the contextual anticipatory pleasure subscale of the TEPS (r=-0.215, p=0.019). Discussion: Our findings showed that individuals with ST, AT and SD exhibited increased activation of the task-positive network, suggesting that these individuals might mobilize more cognitive effort to envision future events compared with controls. Moreover, the findings of decreased activation in the "core network" observed in individuals with ST and AT further suggests that only these individuals, but not those with SD, have prospection impairment. On the other hand, only individuals with ST exhibited hyper-activation of the caudate, thalamus, and claustrum for the positive emotion contrast. These findings suggest that individuals with ST demonstrate a distinct pattern of brain activation while prospecting future events.